Cross-story installation of viscous dampers in timber frame houses for earthquake damage reduction - Nakamura, Yutaka; Matsumura, Ryota (Frontiers in Built Environment, 2022)
Timber frame structures are commonly used in housing construction that use squared-off timber beams, columns, and walls as lateral load-bearing members. A small-size viscous damper can be applied to timber frame houses to reduce damage caused by major earthquakes. Dampers are normally installed inter-story (between adjacent floors) to absorb vibration energy and reduce seismic response. Another method is the cross-story installation wherein a damper is installed between the rooftop and base of the structure across intermediate floors. This study investigated the effectiveness of cross-story installation of a viscous damper by conducting eigenvalue analyses of 2DOF models and earthquake response analyses of a two-story timber frame house subjected to the 2016 Kumamoto earthquake and other major earthquakes. We compared the damping factors and response reduction effects of the cross-story installation with those of conventional inter-story installations. The results showed that the cross-story installation of dampers was more effective than the inter-story installation in terms of reducing story drift. Furthermore, the cross-story installation reduced the number of dampers required for preventing severe damage by half. Finally, the cross-story installation allowed the viscous damper in the 1st story to absorb vibration energy nearly twice as much as that of the inter-story installation. Therefore, while the cross-story damper is typically installed on an outer frame fixed to the house, our results conclude that it can be applied to an existing house as a seismic retrofitting measure.